'Are you gonna show this to white people?': Chicana/o and Latina/o students' counter-narratives on race, place, and representation. Issue 1 (2nd January 2017) - Martínez, Ramón Antonio
Abstract: This article explores the recurring narratives on race, place and representation that emerged in the talk of Chicana/o and Latina/o sixth-graders at a middle school in East Los Angeles, California. Discourse analytic methods are used to closely examine how these narratives were constructed within the contexts of everyday classroom interactions. Drawing on the notion of counter - storytelling from critical race theory, the article highlights how these sixth-grade students articulated counter - narratives about who they were and what their community was like – often in direct opposition to what they perceived as white people's stereotypical assumptions and misperceptions. It is argued that these narratives constitute a powerful and sophisticated critique of dominant narratives that frame working-class Chicana/o and Latina/o students in racist and pejorative terms. The article ends with a discussion of implications for understanding youth agency and the politics of representation.